2021
DOI: 10.3389/fmats.2021.709757
|View full text |Cite
|
Sign up to set email alerts
|

The Verification of Thermoelectric Performance Obtained by High-Throughput Calculations: The Case of GeS2 Monolayer From First-Principles Calculations

Abstract: Electronic fitness function (EFF, achieved by the electrical transport properties) as a new quantity to estimate thermoelectric (TE) performance of semiconductor crystals is usually used for screening novel TE materials. In recent years, because of the high EFF values, an increasing number of two-dimensional materials have been predicted to have the potential for TE applications via high-throughput calculations. Among them, the GeS2 monolayer has many interesting physical properties and is being used for indus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 57 publications
3
11
0
1
Order By: Relevance
“…Moreover, the VBM is mainly contributed by the S- p orbital, while the CBM is occupied by both Ge- s and S- p orbitals. Our results are in accordance with the previous theoretical predicated [ 25 , 46 ], indicating that our calculation parameters are reasonable.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Moreover, the VBM is mainly contributed by the S- p orbital, while the CBM is occupied by both Ge- s and S- p orbitals. Our results are in accordance with the previous theoretical predicated [ 25 , 46 ], indicating that our calculation parameters are reasonable.…”
Section: Resultssupporting
confidence: 93%
“…The side and top views of the GeS 2 monolayer are plotted in Figure 1 a,b, respectively. The relaxed lattice parameters are a = b = 3.44 Å, which agree with previous theoretical predictions [ 21 , 25 ]. Figure 1 c describes the atom orbitals project band structure of the GeS 2 monolayer.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…This structure corresponds to a single slab of the high-pressure, layer-structured, tetragonal CdI 2 -type phase. , To determine the equilibrium lattice parameters of the GeS 2 monolayer, the total energy of the 4 × 4 × 1 supercell of the monolayer as a function of the lattice constant was calculated and is shown in Figure b. We found that the GeS 2 monolayer possesses a symmetry group of P 3̅ m 1 with the lattice constants of a = b = 3.416 Å, which is slightly smaller than previous reports (3.45 Å). The Ge–S bond length in the GeS 2 monolayer is 2.44 Å, which is very different from that of the GeS monolayer in which two types of Ge–S bond lengths are found (2.37 and 2.47 Å). The electronic properties (band structure (BS) and partial density of states (PDOS)) of the GeS 2 monolayer in Figure c,d showed that it is a nonmagnetic semiconductor with a band-gap width of 0.93 eV, which is in good agreement with previous work. It should be emphasized that although the PBE method we used underestimates the band gap width of the GeS 2 monolayer, which was reported to be 1.47 eV by using the HSE06 functional, in this work what we mainly focus on is the change of the band gap before and after molecular adsorption, which will determine the sensitivity of the gas sensor.…”
Section: Resultsmentioning
confidence: 77%